Antimicrobial functionalization of poly(ethylene terephthalate) fabrics with waterborne N-halamine epoxides - Çerkez, İdris; Koçer, Hasan Basri; Worley, S. D.; Broughton, R. M.; Huang, T. S. (Wiley-Blackwell, 2016)
A water dispersible terpolymer of [2-(methacryloyloxy)ethyl]trimethylammonium chloride, glycidyl methacrylate and hydantoinyl acrylamide was synthesized and coated on poly(ethylene terephthalate) fabrics through a pad-dry-cure procedure. The coatings were rendered biocidal upon exposure to dilute household bleach solution. The halogenated fabrics exhibited great antimicrobial functionality with about six logs inactivation of S. aureus and E. coli O157: H7 within only two min of contact time. Moreover, the coatings were found to be very stable against repeated washings and UVA light exposure. It was shown that [2-(methacryloyloxy)ethyl]-trimethylammonium monomer is very useful in preparing waterborne N-halamines which can impart rechargeable, effective, and stable antimicrobial coatings to poly(ethylene terephthalate) fabrics. (C) 2015 Wiley Periodicals, Inc.
Keywords: coatings; functionalization of polymers; polyesters